2000
DOI: 10.1046/j.1468-1331.2000.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in the phenotype, genotype and pathogenesis of different spinocerebellar ataxias

Abstract: Historically, the differential diagnosis of the autosomal ataxias (ADCAs) has been difficult. In 1983 Harding proposed a useful clinical classification. Since 1983 ADCAs have been increasingly characterized in terms of their genetic locus and are referred to as spinocerebeller ataxia (SCA). The overlap between the SCA phenotypes and the high variability within SCA subgroups means that, for individual patients, the underlying mutation cannot be predicted reliable purely on the basis of clinical symptoms and so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Different clinical and neuropathological studies have shown that each SCA specific genetic entity has a constellation of signs and symptoms that are related to disease duration, and with the size of trinucleotide repeat expansion (CAG). Thus, the combination of molecular genetic data and clinical signs provide useful information that serve as the basis for the classification of SCAs (Schelhaas et al, 2000;Stevanin et al, 2000).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Different clinical and neuropathological studies have shown that each SCA specific genetic entity has a constellation of signs and symptoms that are related to disease duration, and with the size of trinucleotide repeat expansion (CAG). Thus, the combination of molecular genetic data and clinical signs provide useful information that serve as the basis for the classification of SCAs (Schelhaas et al, 2000;Stevanin et al, 2000).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In 2000 Schelhaas et al published an interesting study of the pathogenesis of different SCAs as well as the phenotypic and genotypic similarities and differences between the diseases 60 . They emphasized the overlap between the phenotypes of the different forms of SCA as well as the great variation that can be observed in each SCA subtype and stated that a diagnosis should be based on genotype analysis.…”
Section: Spinocerebellar Ataxias Teivementioning
confidence: 99%
“…They emphasized the overlap between the phenotypes of the different forms of SCA as well as the great variation that can be observed in each SCA subtype and stated that a diagnosis should be based on genotype analysis. However, they proposed a clinical algorithm to investigate the various SCAs that takes into account different key signs and symptoms, such as retinal degeneration, eye movement disturbances and the presence of pyramidal signs 60 .…”
Section: Spinocerebellar Ataxias Teivementioning
confidence: 99%
“…General references: O'Donnell and Zoghbi, 1995;Warren and Ashley, Jr., 1995;Monckton and Caskey, 1995;Sutherland and Richards, 1995;Warren, 1996;Schalling, 1996, 1999;Li and el Mallakh, 1997;Koshy and Zoghbi, 1997;Nance, 1997;La Spada, 1997;Mitas, 1997;Tsuji, 1997;Koeppen, 1998;Basu et al, 2000;Schelhaas et al, 2000;Stevanin et al, 2000;Lin et al, 2000;Nussbaum and Auburger, 2000;Morrison, 2000;Cummings and Zoghbi, 2000;Ohara, 2001.…”
Section: Transmission-relatedmentioning
confidence: 99%